National Mapping of the Brazilian Academic Cybersecurity Community - Cordeiro, Kauane; Gomes, Reinaldo Cézar de Morais (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais Estendidos do XXVI Simpósio Brasileiro de CibersegurançaDO - 10.5753/sbseg_estendido.2026.27054, 2026)
This paper presents a methodological workflow for mapping the Brazilian academic cybersecurity community. The approach integrates multiple national databases through a pipeline that encompasses data collection, filtering, curation, automated processing, and the application of data analysis and visualization tools — including word-cloud exploration and a geospatial interactive map. The resulting visualizations reveal regional asymmetries, research clusters, and gaps in academic engagement, enabling an integrated view of the Brazilian cybersecurity ecosystem. The developed framework is reproducible and provides a structured overview that supports strategic planning, community strengthening, and the advancement of collaborative initiatives in cybersecurity.